Capital Taxation under Political Constraints - Florian Scheuer; Alexander Wolitzky (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper studies optimal dynamic tax policy under the threat of political reform. A policy will be reformed ex post if a large enough political coalition supports reform; thus, sustainable policies are those that will continue to attract enough political support in the future. We find that optimal marginal capital taxes are either progressive or U-shaped, so that savings are subsidized for the poor and/or the middle class but are taxed for the rich. U-shaped capital taxes always emerge when the salient reform threat consists of radically redistributing capital and individuals' political behavior is purely determined by economic motives.
Keywords: 330; wealth inequality; capital taxation; coalition formation